A PATIENT WITH CHRONIC HEMODIALYSIS WITH COMORBID ONCOLOGICAL PATHOLOGY – A SERIES OF CLINICAL CASES - Шапкин, Александр Анатольевич; Петерс, Николай Юрьевич; Саруева, Анастасия Павловна; Ооржак, Орлан Валерийович; Мозес, Вадим Гельевич; Мозес, Кира Борисовна (Medicine in Kuzbass, 2020)
The article presents a series of clinical cases of comorbid oncological pathology in patients with chronic hemodialysis. The complexity of treating such patients has been demonstrated.
Keywords: chronic hemodialysis; chronic kidney disease